Konsep Pendidikan Akhlak Menurut Ahmad Tafsir - Aziz, M Ginanjar; Jamal, Moh. Yusup Saepuloh (Prodi PAI IAILM Suryalaya, 2024)
In this life, humans cannot be separated from education. In this study the authors have several underlying reasons including First, without prejudice to the role of other characters, that this character is very concerned about human behavior. Second, this figure has explored the problem of human nature and the perfect human being according to Islam with its various characteristics and the perspective of Islamic education. In this study the authors used qualitative data types. The method used in this qualitative research was interview, observation, documentation techniques. In this study, the data analysis technique used by researchers used the Miles and Huberman model. Activities in data analysis, namely, data reduction, data display, and conclusion drawing/verification. As for the data validity test that can be carried out, namely the Credibility Test of the triangulation type of Moral Education in Ahmad Tafsir's view is guidance given by someone to someone so that he develops optimally in accordance with Islamic teachings whose curriculum must contain the values of faith and morals as its foundation. Ahmad Tafsir is the goal that leads people to become true Muslims. perfect, Ahmad Tafsir's moral education curriculum should be structured based on educational goals according to Islam. Prof's thoughts Ahmad Tafisr regarding moral education should be used as a reference for the development of education in the present and in the future.